STRATEGI PENGAWASAN KANTOR IMIGRASI KELAS II TPI TANJUNG BALAI KARIMUN TERHADAP KEDATANGAN DAN KEBERANGKATAN WARGA NEGARA ASING DI PELABUHAN INTERNASIONAL TANJUNG BALAI KARIMUN - Ritonga, Melisa Surya Ningsih; Mardalena, Tri; Rachman B, Arief (Fakultas Ekonomi Universitas IBA, 2021)
This research begins with an increase in foreign traffic, including in Indonesia, so that it gives a positive impact on the development of the territory of Indonesia. In addition, the entry and exit of foreign citizens also have an adverse impact on national security and defense. Seeing the large number of Foreign Citizens entering and exiting through the immigration center (TPI) of Tanjung Balai Karimun international port, it is necessary to monitor the traffic of the Foreign Citizens. This research intend to know any supervision strategy and how the implementation of supervision strategy that did by class II imigration office TPI tanjung balai karimun against the arrival and Foreign's departure in tanjung balai karimun international port . This research was implemented at the Tanjung Balai Karimun International Immigration Center. This research is descriptive by the qualitative approach. Research data is collected through the observation, the interview , and the documentation. After that the data will be analyzed using inductive analysis and tested its validity using the triangulation. According to the data analysis that have done by the supervision strategy and carried out by immigration officers at the Tanjung Balai International Immigration Center (TPI), Tanjung Balai Karimun, was doing the careful inspection and tightening the supervision by the operational standard and the legislation. This case shows supervision that did by the immigration officer is corresponding to the operational standard and the applicable law.